2016
DOI: 10.1039/c6tc00238b
|View full text |Cite
|
Sign up to set email alerts
|

High mobility transistors based on electrospray-printed small-molecule/polymer semiconducting blends

Abstract: Spray-coating techniques have recently emerged as especially effective approaches for the deposition of small semiconducting molecules toward the fabrication of organic field-effect transistors (OFETs). Despite the promising mobility values and the industrial implementation capability of such techniques, the resulted devices still face challenges in terms of morphology control and performance variation. In this work, the efficient process control of electrostatic spraying deposition (ESD) and the excellent fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…The active semiconducting layer of the blended‐OPT contains only 9 wt% of OSC, while the major component of the film is the PLA. It has been reported that blending polymer into the OSCs can significantly reduce the material cost and enhance the processability by cost‐efficient solution methods during OFET fabrication . Here, we demonstrated that blending the PLA into the OSC could lead to OFETs with decent transistor characteristics and enhanced photosensitivity.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The active semiconducting layer of the blended‐OPT contains only 9 wt% of OSC, while the major component of the film is the PLA. It has been reported that blending polymer into the OSCs can significantly reduce the material cost and enhance the processability by cost‐efficient solution methods during OFET fabrication . Here, we demonstrated that blending the PLA into the OSC could lead to OFETs with decent transistor characteristics and enhanced photosensitivity.…”
Section: Resultsmentioning
confidence: 60%
“…Blending OSCs with polymers in the conducting channels can provide the device with a large area of interaction interface, and thus is expected to enhance the photosensitivities of aforesaid novel OPTs. Meanwhile, fabrication of OPTs combining OSC and polymer blends effectively reduces the material cost, provides the devices with better flexibility, and importantly, tunes the OSCs properties to make the semiconducting materials printable . In this work, OPTs based on blended structure (blended‐OPTs) and layered structure (layered‐OPTs) were both fabricated by using a common soluble OSC 2,7‐dioctyl[1]benzothieno[3,2‐b][1]benzothiophene (C8‐BTBT) and an insulating biopolymer polylactide (PLA), and the photoresponse performances of both OPTs under UV light were investigated and compared.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the impact of fabrication techniques on the versatile blend system has been demonstrated a number of times over the years. Examples of fabrication techniques include spray deposition, line printing, air brushing, inkjet printing, dipping processes, vertical flow, blade coating, and off‐center spin coating …”
Section: Molecular Semiconductor/polymer Blendsmentioning
confidence: 99%
“…This is expected from such measurements due to a reduction in the trapping rate as the trap states become occupied. To quantify the bias-stress effect in the two blend systems, we fitted a stretched exponential function to the experimental data using: [1] [20] [72]…”
Section: Figure 3cmentioning
confidence: 99%